2019
DOI: 10.1080/0886022x.2019.1662440
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of estimated glomerular filtration rate prior to surgery in postsurgical acute kidney injury among very elderly patients: a retrospective cohort study

Abstract: Background: Acute kidney injury (AKI) is a common complication after surgery. Because of unpredictable and variable age-dependent physical decline, the incidence, risk factor of postsurgical AKI and the predictive power of estimated glomerular filtration rate prior to surgery (eGFRpreSurg) has not been fully elucidated in very elderly patients.Methods: All discharged patients aged ≥80 years without chronic kidney disease who underwent surgery prior to intensive care unit (ICU) admission from 2017 through 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Glomerular filtration rate (GFR) was an important factor in determining AKI incidence in post-cardiac surgery subjects. Preoperative eGFR is a risk factor for postoperative AKI, and subjects with a preoperative eGFR of 70 mL/min/1.73m 2 have a higher incidence of AKI (26). Meta-analysis study on eGFR value before CPB operation showed a correlation between low eGFR value with AKI where preoperative GFR of <30 mL/min/1.73m 2 was a risk factor of postoperative AKI and increases the risk of AKI for more than 4,000 times (8,15,26,27).…”
Section: Resultsmentioning
confidence: 99%
“…Glomerular filtration rate (GFR) was an important factor in determining AKI incidence in post-cardiac surgery subjects. Preoperative eGFR is a risk factor for postoperative AKI, and subjects with a preoperative eGFR of 70 mL/min/1.73m 2 have a higher incidence of AKI (26). Meta-analysis study on eGFR value before CPB operation showed a correlation between low eGFR value with AKI where preoperative GFR of <30 mL/min/1.73m 2 was a risk factor of postoperative AKI and increases the risk of AKI for more than 4,000 times (8,15,26,27).…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent retrospective cohort study of 668 very elderly (≥80 years) patients, the estimated GFR before surgery, calculated based on the Modification of Diet in the Renal Disease Study equation, is a risk factor for postoperative AKI (OR 2.662, 95% CI 1.264–5.608; P = 0.01). The incidence of postoperative AKI is significantly higher among patients with lower preoperative estimated GFR than among those with estimated GFR ≥70 mL/min/1.73 m 2 ( P = 0.003) [ 19 ]. Although their work has many limitations in interpretation (such as neglecting various surgical burdens), late postoperative factors, AKI duration, and preoperative estimated GFR can help evaluate postoperative AKI.…”
Section: Renal Function Testmentioning
confidence: 99%
“…Sir, By a retrospective cohort study, Wu and colleagues [1] assessed predictive role of preoperative estimated glomerular filtration rate (eGFR) for postoperative acute kidney injury (AKI) in very elderly surgical patients and showed that eGFR could be used as an index for AKI risk stratification. This study has potential clinical implications, but we noted several issues that wished to remind readers for attention and obtain the authors' comments.…”
Section: Letter To the Editormentioning
confidence: 99%